Influencing of Organizational Culture, Leadership Style, and Work Stress to The Turnover Intention of Employees Stella Maris Education Foundation Jakarta - Augustine Priyowidodo; Wibowo; Hamidah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
The purpose of this study was to determine the effect of Organizational Culture, Leadership Style and Job Stress on Turnover Intention. This study uses a quantitative approach with survey method and path analysis to analyze the effect of Organizational Culture, Leadership Style and Job Stress on Turnover Intention. The sample for this reseach are 95 employees from 125 employees. The techniques analyzis data was descriptive statistics and inferential analysis that were tested using normality test error estimate a simple regression, linearity test and path analysis. The result shows that organizational culture gives negative direct effect on Turnover Intention, Leadership Style gives negative direct effect on Turnover Intention, Job stress gives positive direct effect on turnover intention, organizational culture gives negative direct effect to job stress, leadership style gives negative direct effect to job strees and ledearship organization gives positive direct effect to leadership style.